2006
DOI: 10.3102/01623737028002131
|View full text |Cite
|
Sign up to set email alerts
|

High School Exit Examinations and State-Level Completion and GED Rates, 1975 Through 2002

Abstract: This article investigates the extent to which state-mandated high school exit examinations are associated with state-level public high school completion rates in the United States. The authors estimate a series of state and year fixed effects models using a new measure of state-level public high school completion rates and archival information about states’ policies on high school exit examinations from 1975 through 2002. The study finds that state high school exit examinations—particularly the “more difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 21 publications
4
76
0
Order By: Relevance
“…However, it has been suggested that such high stakes exams have adverse impacts that prompt minority and low-achieving students to leave high school early (CEP, 2006;Garcia and Gopal, 2003;Jacob, 2001;Warren, Jenkins, and Kulick, 2006). Furthermore, despite the vast and rapid adoption of the policy, there is very little causal research on the benefits of the HSEE including whether the exam effectively raises students' academic skills.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it has been suggested that such high stakes exams have adverse impacts that prompt minority and low-achieving students to leave high school early (CEP, 2006;Garcia and Gopal, 2003;Jacob, 2001;Warren, Jenkins, and Kulick, 2006). Furthermore, despite the vast and rapid adoption of the policy, there is very little causal research on the benefits of the HSEE including whether the exam effectively raises students' academic skills.…”
Section: Introductionmentioning
confidence: 99%
“…An exit exam is designed to test all subject matter learned during high school in a comprehensively fashion. The introduction of the HSEE as a graduation requirement can be traced to the 1980s 9 when the report A Nation at Risk (1983) 10 called for higher standards and expectations including the use of standardized tests to improve the academic underachievement of U.S. students compared to other advanced countries (Dee, 2002;Dee and Jacob, forthcoming;Harris and Herrington, 2006;Warren et al 2006). …”
Section: Overview Of the High School Exit Exam In The U Smentioning
confidence: 99%
See 3 more Smart Citations